2020
DOI: 10.2196/16538
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a Heart Failure Telemonitoring Program Implemented as the Standard of Care in an Outpatient Heart Function Clinic: Pretest-Posttest Pragmatic Study

Abstract: Background Telemonitoring (TM) can improve heart failure (HF) outcomes by facilitating patient self-care and clinical decisions. The Medly program enables patients to use a mobile phone to record daily HF readings and receive personalized self-care messages generated by a clinically validated algorithm. The TM system also generates alerts, which are immediately acted upon by the patients’ existing care team. This program has been operating for 3 years as part of the standard of care in an outpatien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
102
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(105 citation statements)
references
References 40 publications
2
102
0
1
Order By: Relevance
“…An RCT conducted with Medly at the Heart Function Clinic and an evaluation of the Medly Program as part of the standard of care found improvements in patient health outcomes and high patient and health care provider satisfaction. Adherence to daily monitoring was high, and the cardiologists and nurse practitioners indicated that Medly improved information transfer from their patients because they received real-time patient information and alerts that supported clinical decision making [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…An RCT conducted with Medly at the Heart Function Clinic and an evaluation of the Medly Program as part of the standard of care found improvements in patient health outcomes and high patient and health care provider satisfaction. Adherence to daily monitoring was high, and the cardiologists and nurse practitioners indicated that Medly improved information transfer from their patients because they received real-time patient information and alerts that supported clinical decision making [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…There have been several studies across a variety of specialties that appear to show that virtual visits do not worsen outcomes, and in some cases even improve care. [3][4][5][6][7] Two studies within the field of urology have been completed showing no adverse outcomes in a general urology virtual followup clinic and in a virtual clinic focused on renal colic. 8,9 With the fluid nature of a pandemic scenario, it is unclear when we will once again have access to surgical and clinical resources to provide the standard care for our patients.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, digital health interventions have recently been developed to simplify the process of managing and tracking the symptoms of HF [10][11][12][13][14][15][16][17][18][19]. One such intervention, which was developed alongside HF patients and clinicians living in Canada, has been shown to improve patient self-care and quality of life amongst Canadian HF patients [19,20].…”
mentioning
confidence: 99%